The Impact Of Compensation And Work Environment On Employee Performance At A Cable Company - Zainal Musthafa; Ade Suhara; Sevty Auliani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to analyze the effect of compensation and work environment on employee performance at CV Bintang Timur Mandiri. Using a quantitative approach with a sample of 40 employees, this study found that compensation significantly positively affects employee performance, with a t-value of 2.685, more significant than the t table of 1.685. On the other hand, the work environment does not significantly affect employee performance, with a t-value of -0.176, which is smaller than the t table of 1.685. However, compensation and work environment simultaneously affect employee performance with a calculated F value of 10.501, greater than the F table 3.25. The results of this study indicate the importance of providing fair compensation, creating a comfortable work environment, increasing motivation through training and recognition of achievements, and managing human resources well. These steps will contribute to the productivity and positive image of the company. Keywords: Compensation, Work Environment, Employee Performance